Louis-Ferdinand Céline: Trolling For Another Time? - Warde, Luke (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2021)
This article presents a reading of Louis-Ferdinand Céline through the concept of trolling. A relatively new phenomenon, trolling denotes an attempt to elicit a negative response in a chosen target via deliberate provocation or incitement. While inextricable from the online social media platforms that have facilitated its emergence as a discursive mode, trolling is dependent on rhetorical strategies that are hardly new: irony, self-referentiality, effrontery, aggression, etc. Trolls seek to cultivate a brand around the antipathy they delight in triggering. I contend that Céline attempted to do just this in the postwar period, and more specifically in the series of interviews he conducted at Meudon in the last decade of his life. I thus argue against some recent scholarship that claims that Céline attempted to regain, by expressing contrition, a sympathetic audience following his condemnation for having published a series of egregiously antisemitic pamphlets. Rather, I suggest that he sought to instrumentalize his notoriety for his own advantage; some readers, he likely reasoned, are drawn to him because, not in spite of, his infamy. My argument draws on a body of recent writing on the relationship between humour, new media and far-right politics.